Clustering of Paddy Harvest Productivity in Each Village of Jember Regency Using K-Means Clustering and Davies Bouldin Index - Astika, Hestina Restu; Nilogiri, Agung; A’yun, Qurrota (Primakara University, 2026)
Paddy (Oryza sativa L.) is a cultivated crop that serves as the staple food source for the majority of the Indonesian population. East Java Province is one of the largest paddy-producing provinces in Indonesia. Jember Regency, as one of the paddy production centers in East Java, has a relatively high production level each year. However, there is currently no system available that clusters paddy data at the village level in the form of map-based visualization. This study aims to cluster the paddy harvest productivity of each village in Jember Regency based on the variables of planted area, harvested area, and paddy production for the years 2022 and 2023 using the K-Means Clustering algorithm and the Davies Bouldin Index (DBI). The data used in this study were obtained from the official publications of the Jember Regency Bureau of Statistics, covering a total of 248 villages. The clustering process was carried out by testing the number of clusters (k) from 2 to 10, which were then evaluated using DBI to determine the optimal number of clusters. The results show that the optimal number of clusters is 3, with a DBI value of 0.6053. This DBI value indicates that the quality of clustering of planted area, harvested area, and paddy production is considered good. The clustering results consist of 40 villages in Cluster 1, 105 villages in Cluster 2, and 103 villages in Cluster 3. The clustering results were implemented into a web- based Geographic Information System using the Flask Python framework and the Leaflet library to display an interactive map in GeoJSON format. This study is expected to provide benefits for the Jember Regency Bureau of Statistics, the community, and farmers in storing, managing, and providing information related to paddy production in Jember Regency.